(untitled) (Journal of the College of Basic Education, 2023)
The plot is a term that must be present in all literary genres such as story , novel or theatrical text in order to act as interconnection of events and their sequences since the first moment of first conflict of text structure .Therefore the researcher has designed developed theatrical text structure according to science philosophy perspective through following scientific revolutionary structure stages of philosopher ( Thomas Koon ) . I exposed this The research to a group of professors and experts in which they welcomed and accepted by everyone .Accordingly the researcher has chosen one sample for text analysis by following content analysis methodology in adaption method and text division into eight sequenced stages as in (The idea and its opposite, crises or problem , instructional sample , external aspects , quantification accumulation , sensory perception , changing point , results and reason ) . The researcher has reached a set of results such as : Proposed construction sequence according to first seven stages , sequenced structure achieving developed moral and positive correlation referring to individual self – secondary school student except if that the eighth step b( reason and results) was weak and unclear prosaic ending in which lead to confusion and return the subject to the same point or without completing Developmental rotation .